Evaluasi pertanggungjawaban Anggaran Pendapatan dan Belanja Desa (APBDes) di Desa Patokaan Kecamatan Talawaan - Ponto, Endang Sri Ayu; Tinangon, Jantje J.; Afandi, Dhullo (Riset Akuntansi dan Portofolio Investasi, 2024)
Regional autonomy is a fundamental right, authority, and obligation of an autonomous region. It entails the ability to regulate and manage government affairs and the interests of local communities in accordance with statutory regulations. The central government has implemented regional autonomy to empower regional governments to manage their own affairs without interference. This research aims to determine whether the Village Revenue and Expenditure Budget (APBDes) in Patokaan Village is in compliance with Law Number 20 of 2018. The data analysis method used is qualitative research with a descriptive approach. The research results clearly show that the accountability of the Village Revenue and Expenditure Budget (APBDes) in Patokaan Village is in line with the regulations set out in Home Affairs Government Number 20 of 2018 concerning Village Financial Management. Specifically, the village government has submitted an accountability report in a timely and transparent manner to the Village Consultative Body (BPD) and the community through an information board on the design and realization of the 2023 Village Revenue and Expenditure Budget.